Biodiesel Synthesis from Palm Fatty Acid Distillate (PFAD) by Palm Oil Industry Product using Metal-Hydroxyapatite Catalyst. (October 2020) - Muria, Sri Rezeki; Azis, Yelmida; Khairat,; Putri, Desy Erika; Zultiniar,; Syafruddin,
Abstract: Hydroxyapatite (HAp, Ca10 (PO4 )6 (OH)2 ), has been successfully synthesized hydrothermally from eggshells or shells through the formation of Precipitate Calcium Carbonate (PCC). For biomedical applications, some synthesized HApare still calcium deficient (HApdc ), so they do not meet specifications as implants or fillers of bone and teeth. Because it is resistant to high temperatures and has pores, in this study HApdc used as a catalyst for the synthesis of biodiesel from palm fatty acid (PFAD). In the initial stage, HAp is impregnated with metals: Cu, Co and Ni and produces catalysts Cu-HAp, Co-HAp and NI-HAp. Furthermore, the metal-HAp catalyst is used in the PFAD esterification process into biodiesel. PFAD has free fatty acid (ALB) levels reaching 90%. Cu-HAp catalyst, giving the highest conversion yield of biodiesel (94.4%), with specific gravity 0.84 g/ml (40 ° C, viscosity 4, 811 Cst, acid number 0.5533 gr KOH / gr oil, flash point 120 ° C and a calorific value of 9813 Kcal/kg in accordance with ISO standards-04-7182-2006. Analysis of the chemical components in the form of biodiesel from PFAD: Methyl Ester Heksadekanoat (53.1%); ME 9, Oktadekenoat (32.81%); ME octadecanoic (2:59 %) and ME 9, 12, Octadecadienoic (5.93%) and a little Hexadecanoic Acid (5.57%).